Molecular monitoring of the diversity of human pathogenic malaria species in blood donations on Bioko Island, Equatorial Guinea - Tobias Schindler; Tamy Robaina; Julian Sax; Jose Raso Bieri; Maximilian Mpina; Linda Gondwe; Ludmila Acuche; Guillermo Garcia; Carlos Cortes; Carl Maas; Claudia Daubenberger (Malaria Journal, 2019)
Abstract Background Malaria can be transmitted by blood transfusion from human to human and it is responsible for the majority of transfusion-transmitted infectious diseases worldwide. In sub-Saharan Africa, it had been estimated that almost a quarter of blood donations contain malaria parasites. Since rapid diagnostic tests and thick blood smear microscopy lack sensitivity for low density parasitaemia, particularly in asymptomatic adults, the most reliable method to assess the problem of transfusion-transmitted malaria are nucleic acid-based molecular approaches such as quantitative polymerase chain reaction. The study was undertaken to determine the prevalence of sub-microscopic malaria parasite infection among blood donors in Malabo, Equatorial Guinea. Methods Between July and August 2017, a total of 200 individual blood samples from blood donors at the Malabo Blood Bank were collected and screened by rapid diagnostic tests and thick blood smear microscopy. Retrospectively, the same samples were analysed for the presence of undetected, low-density malaria parasites using quantitative polymerase chain reaction. Results In comparison to 6.5% (13/200) by rapid diagnostic test and 2.0% (4/200) by microscopy, the proportion of Plasmodium falciparum positive blood donations analysed by quantitative polymerase chain reaction was significantly higher (26%, 52/200). Densities of P. falciparum positive blood donations were ranging from 0.06 to 3707.0 parasites/µL with 79.6% below 100 parasites/µL and therefore not detectable by non-molecular malaria diagnostic tests. qPCR based species identification revealed that P. falciparum was the dominating species responsible for 88.1% (52/59) of positive blood donations, followed by Plasmodium malariae (15.3%, 9/59) and Plasmodium ovale (3.4%, 2/59). Conclusions This study confirms that in malaria endemic settings, sub-patent malaria infections among blood donors are prevalent. In blood collected from healthy donors living in Malabo, P. falciparum, P. malariae and P. ovale ...